Fatty acid methyl ester production from Calophyllum inophylllum oil by two-step process using sulfonated tio2-sio2 catalyst - Kamarullah, Shahida Hanum; Mustafa, Nur Atirah (GADING Journal of Science and Technology, 2024)
The worldwide search for sustainable alternative energy sources has been sparked by the depletion of fossil fuel supplies and the environmental issues related to their production and burning. Fatty acid methyl esters (FAME), often known as biodiesel, is one of the sustainable fuels recently promoted. This fuel which usually uses edible oil or non-edible oil as feedstock has emerged as a promising substitute for conventional fossil fuels due to its renewable nature, lower emissions profile, and potential for carbon neutrality. Usually, homogeneous catalysts are often used in this production of biodiesel; however, heterogeneous catalysts become preferable due to ease of separation and cost effectiveness. Heterogenous solid acid catalyst on the other hand, has been proven to increase the reaction process, separate easily and be recycleable while supported by the catalyst from biomass waste. Rice husk ash (RHA) which produces silica from biomass waste, can be considered affordable, widely available and able to eliminate waste problem. The potential of sulfonated SiO2-TiO2 as a binary catalyst that could address both the challenges of high FFA content and improve biodiesel yields through enhanced catalytic activity is underexplored. Therefore, in this study, sulfonated TiO2-SiO2 catalyst was optimized for the esterification and transesterification of Calophyllum inophyllum oil into methyl esters. A two-step reaction process was performed by using sulfonated TiO2-SiO2 as solid acid catalyst in esterification process and followed by base-catalysed transesterification using potassium hydroxide, KOH. The analysis on the optimization of the reaction parameters revealed that the higher conversion of biodiesel production of 65.50% was achieved using 9:1 methanol to oil ratio, 3 wt% of catalyst loading at 65°C for 1 hour. Gas chromatography mass spectrometry (GC-MS) showed seven of the methyl ester peaks that were obtained at optimized reaction parameters. Therefore, solid catalyst, sulfonated TiO2-SiO2, has the ability to be used as an alternative catalyst for FAME production from C. inophyllum oil.